Evaluation of the social-cultural competitiveness of cities based on sustainable development approach - Komasi, Hossein; Zolfani, Sarfaraz Hashemkhani; Nemati, Alireza (Decision Making: Applications in Management and Engineering, 2023)
The terms of competitiveness at the level of places and sustainable development were created in the 1980s and 1990s. In the beginning, most researchers emphasized the dimension of economic competitiveness, but in recent decades, other aspects of competitiveness, such as socio-cultural and environmental, have been highlighted. The aim of the present research is evaluation the social-cultural competitiveness in the city of Kermanshah based on a sustainable development approach. This research is descriptive and analytical, the TOPSIS model was used for data analysis, and Entropy was used to weight the indicators. After applying the weight of the indicators in the TOPSIS model, The research findings showed that the city of Kermanshah in the TOPSIS model, ranks 15th with a coefficient of 0.209; in the MABAC model, ranks 14th with a coefficient of -0.116 and in the EDAS model, ranks 14th with a coefficient of 0.122579271 is in the last and 14th position of socio-cultural competitiveness. The results showed that; Considering the nature of urban competitiveness, which is multidimensional, it is necessary to avoid a one-sided approach in urban competitiveness planning and to consider the socio-cultural, environmental, and security dimensions of urban competitiveness in an integrated manner. To improve the competitiveness of Iranian cities, while paying attention to the internal competitive advantages of the 15 studied cities, special attention should be paid to the fields of economic, environmental, socio-cultural, and security competitiveness. Each of these cities concerns their competitive role in transnational dimensions. This requires special attention to the national macro-plans.